Students' Perception on The Use of Pear Deck on English Learning - Qiamulail, Nisa Qonita; Sujannah, Wahyu Diny (Universitas PGRI Madiun, 2024)
Teachers need to encourage passive students to be more active during the teaching and learning process. One of the platforms that can be used to address this issue is Pear Deck due to its anonymous feature. This survey research was conducted to examine students' perceptions on the use of Pear Deck to learn English. The participants were 41 third-grade students in one of the junior high schools in Malang who had used Pear Deck in English learning in the class. The data were collected through a five-point Likert scale questionnaire. The findings revealed that the students perceived Pear Deck to be easily operated and beneficial to facilitate their English learning. Additionally, this platform also made them enjoy the process of learning English in the class, so they wanted to use it again for further learning. Therefore, it is recommended that English teachers start using Pear Deck as the teaching platform and optimize the use of Pear Deck’s interactive slides to attract students' interest in learning English. Moreover, it is also suggested that future researchers examine teachers' perceptions on the use of Pear Deck as an interactive learning tool in teaching English